1998
DOI: 10.1037/h0087283
|View full text |Cite
|
Sign up to set email alerts
|

Target speed alone influences the latency and temporal accuracy of interceptive action.

Abstract: When intercepting a mobile object or an apparent movement, participants show a temporal bias. They are in advance when dealing with a slow-moving stimulus and late with a fast-moving one. We studied participants intercepting an apparent movement by sliding a disk on a table. Using a fast and a slow stimulus speed, we varied three factors: duration of presentation of the stimulus, distance covered by the stimulus, and speed context (constant or varied) of stimulus presentation. In addition to the temporal bus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…This raises the possibility that any effects of target speed on performance could actually be effects of the changes in viewing distance. Previous experiments have shown that VT and/or target speed affect performance (Ball, 1992;Ball & Glencross, 1985;Brouwer, Brenner, & Smeets, 2000, 2002De Lussanet, 2001;Fleury, Basset, Bard, & Teasdale, 1998;Laurent et al, 1994;Mason & Carnahan, 1999;Montagne et al, 2000) but have not shown any independent effect of viewing distance, leading to the conclusion that it is not viewing distance that affects performance but VT (e.g., Fleury et al, 1998;Mason & Carnahan, 1999;Montagne et al, 2000), target speed (e.g., Brouwer et al, 2000Brouwer et al, , 2002, or both (e.g., Ball & Glencross, 1985). Furthermore, whilst it is relatively straightforward to give functional interpretations to the finding that shorter VTs and faster targets elicit briefer, faster responses (see above and Discussion section), it is not easy to explain why greater viewing distances should elicit briefer, faster responses.…”
Section: Methodsmentioning
confidence: 98%
“…This raises the possibility that any effects of target speed on performance could actually be effects of the changes in viewing distance. Previous experiments have shown that VT and/or target speed affect performance (Ball, 1992;Ball & Glencross, 1985;Brouwer, Brenner, & Smeets, 2000, 2002De Lussanet, 2001;Fleury, Basset, Bard, & Teasdale, 1998;Laurent et al, 1994;Mason & Carnahan, 1999;Montagne et al, 2000) but have not shown any independent effect of viewing distance, leading to the conclusion that it is not viewing distance that affects performance but VT (e.g., Fleury et al, 1998;Mason & Carnahan, 1999;Montagne et al, 2000), target speed (e.g., Brouwer et al, 2000Brouwer et al, , 2002, or both (e.g., Ball & Glencross, 1985). Furthermore, whilst it is relatively straightforward to give functional interpretations to the finding that shorter VTs and faster targets elicit briefer, faster responses (see above and Discussion section), it is not easy to explain why greater viewing distances should elicit briefer, faster responses.…”
Section: Methodsmentioning
confidence: 98%
“…Consequently, one way of revealing underlying differences in lateralisation might be by increasing the complexity of tests used for assessing hand skill. Since in coincidence-anticipation tasks involving complex movement sequences the timing accuracy depends on coordination between time to initiate the movement and on anticipation and modulation of movement time (Fleury, Bard, Teasdale, Michaud, & Lamarre, 1999;Fleury, Basset, Bard, & Teasdale, 1998), these variables will also be analysed.…”
Section: Rodrigues Et Almentioning
confidence: 99%
“…It is assumed that the movement is pre-programmed before its initiation and that visual information obtained up until the moment of movement execution plays a critical role in successful performance ( Tresilian & Houseman, 2005 ;. Spatial and temporal accuracy are known to be infl uenced by constraints imposed by the moving target (e.g., Fleury, Basset, Bard, & Teasdale, 1998 ;Tresilian & Houseman, 2005 ) and the interceptive action required (e.g., Dubrowski & Carnahan, 2001 ;Tresilian & Plooy, 2006 ), as well as gaze control related to the moving target (e.g., Rodrigues, Vickers, & Williams, 2002 ).…”
mentioning
confidence: 99%